TricIA: A Multi-Agent System to Facilitate Interaction with Business Intelligence Dashboards - Raviolo, Bruno; Chaves, Joan Lucas M. S.; Holanda Filho, Raimir; Caminha, Carlos (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
This paper presents TricIA, a multi-agent system based on an open-source language model with 12 billion parameters, designed to enhance the usability of the Monitor Fiscal — a business intelligence platform from the Court of Accounts of the State of Ceará. TricIA acts as a chatbot that assists users in navigating and understanding the available data, both through natural language responses and by performing direct actions on the interface, such as page redirections and filter applications. To ensure efficiency even on modest infrastructures, an architecture composed of three specialized agents was adopted: the orchestrator, the guardrail, and the function-calling agent. This structure distributes responsibilities and allows smaller models to overcome capacity limitations. The paper describes the architecture, integration techniques with the dashboards, and presents a functional demonstration of the system, highlighting its potential to democratize access to complex fiscal information.